Autonomous Control for a Reliable Internet of Services: Methods, Models, Approaches, Techniques, Algorithms, and Tools - Ganchev, Ivan; van der Mei, R. D.; van den Berg, Hans (Computer Communication Networks and Telecommunications, 2018)
cloud computing; communication channels; information theory; computer networks; computer systems; data communication systems; Human-Computer Interactopm (HCI); internet; Internet of Services (IoS); Internet of Things (IoT); multimedia systems; quality of experience (QoE); quality of service (QoS); telecommunication networks; telecommunication traffic; user interfaces